Challenges to effective cancer control in China, India, and Russia - Goss, Paul E; Strasser-Weippl, Kathrin; Lee-Bychkovsky, Brittany L; Fan, Lei; Li, Junjie; Chavarri-Guerra, Yanin; Liedke, Pedro E R; Pramesh, C S; Badovinac-Crnjevic, Tanja; Sheikine, Yuri; Chen, Zhu; Qiao, You-lin; et al. (The lancet oncology, 2014)
Cancer is one of the major non-communicable diseases posing a threat to world health. Unfortunately, improvements in socioeconomic conditions are usually associated with increased cancer incidence. In this Commission, we focus on China, India, and Russia, which share rapidly rising cancer incidence and have cancer mortality rates that are nearly twice as high as in the UK or the USA, vast geographies, growing economies, ageing populations, increasingly westernised lifestyles, relatively disenfranchised subpopulations, serious contamination of the environment, and uncontrolled cancer-causing communicable infections. We describe the overall state of health and cancer control in each country and additional specific issues for consideration: for China, access to care, contamination of the environment, and cancer fatalism and traditional medicine; for India, affordability of care, provision of adequate health personnel, and sociocultural barriers to cancer control; and for Russia, monitoring of the burden of cancer, societal attitudes towards cancer prevention, effects of inequitable treatment and access to medicine, and a need for improved international engagement.